Defending Christianity from the ‘rainbow plague’: Historicised narratives of nationhood in the anti-genderism register in Poland - Baran, Dominika (Gender and Language, 2023)
Building on previous work on the anti-genderism register and moments of enregisterment, and adopting the Discourse-Historical Approach with its notion of topoi as an argumentation device used by right-wing populists, this article examines how the Catholic Church and right-wing politicians and media have mobilised against the alleged threat of ‘LGBT/gender ideology’ in Poland. Based on the analysis of 70 texts including homilies, political speeches, news articles and interviews, the article identifies three content-related topoi that are relayed across various anti-genderist actors. Together, these topoi and their repeated reuptake help to construct a historicised narrative of Poland as the defender of Christianity and of Europe, and to legitimise different actors’ anti-LGBT campaigns as they pursue their particular agendas. The article makes a contribution to exploring the processes through which the globally circulating anti-genderism register operates in a specific local context.